My companion in life - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
'Spore is my companion', discloses Simão Mbonani, who works for Save the Children in Luanda, Angola. 'Both in the office and in the farmers fields, especially when I want to share the news in Spore. The magazine is passed from hand to hand among...